Concurrent validity of the Canadian Occupational Interest Inventory and the Self Directed Search for high school students in specified subject areas - Fitzsimmons, George; Melnychuk, Don A. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study investigated: (a) the ability of the Canadian Occupational Interest Inventory (COII) and the Self Directed Search (SDS) to discriminate among Grade 12 students in 8 different subject areas; (b) the inter-scale correlations of the COII and the SDS; and (c) the relationship between the student groups' COII and SDS interest patterns and external reference points. In general, the findings indicate that the COII and the SDS scales tend to effectively discriminate among the subject areas. The correlation coefficients of similar scales for the two inventories were found to be significant. In sum, the results of the study lend some support to the concurrent validity of the COII and the SDS for high school students.